The Impact of Marijuana Legalization on Alcohol Consumption in the United States (2002-2019) : A Difference-in-Differences Analysis - Stočes, Dominic; Čihák, Jakub; Máslo, Lukáš Augustin, 1985-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2024)
This bachelor's thesis analyzes the impacts of marijuana legalization on alcohol consumption between 2002 and 2019 in the United States using the difference-in-differences method. The thesis aims to determine whether marijuana and alcohol exhibit more characteristics of economic substitutes or complements. The analysis concludes that it was not possible to prove a causal relationship between the legalization of marijuana and alcohol consumption based on the data used. However, the results tend to support the presence of a substitution effect between the two substances. This finding contributes to a better understanding of the interaction between both substances and allows for better prediction of the potential impacts of marijuana legalization. The main contribution of this work is the addition to the economic debate examining the relationship between the two drugs.
Vedoucí práce: Jakub Čihák
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses